Hatch timing of two subarctic salmonids in a stream network estimated by otolith increments. (29th June 2021) - Fitzgerald, Kevin A.; Haworth, Matt R.; Bestgen, Kevin R.; Farrell, Collin J.; Utsumi, Shunsuke; Kishida, Osamu; Uno, Hiromi; Kanno, Yoichiro
Abstract: Hatch timing in autumn‐spawning stream salmonids is poorly understood in the subarctic region because snow cover prevents direct sampling of cryptic early life stages. Otolith micro‐increment analysis was used to infer hatch dates of white‐spotted charr Salvelinus leucomaenis (Pallas) and masu salmon Oncorhynchus masou (Brevoort) in a mainstem‐tributary network in northern Japan. Accuracy and precision were validated by ageing hatchery individuals with known hatch date ranges. In July 2018, 93 wild young‐of‐the‐year white‐spotted charr and 81 masu salmon were collected and aged. Masu salmon hatched, on average, 24 days earlier (mean = February 8) than white‐spotted charr (March 4), and hatch dates spanned a minimum of 2 months for each species. In masu salmon, hatch dates of individuals collected in the mainstem were nearly 3 weeks earlier than those in a tributary. This study provided knowledge on intra‐ and inter‐specific variation in hatch timing of native salmonids in a subarctic stream network.